Enhancement of Human Gingival Fibroblasts Bioactivity and Proliferation on Plasma Sprayed Yttria-Stabilised Zirconia/TiO2 Surface Coating of Titanium Alloys: An In-Vitro Study - Jemat A.; Razali M.; Otsuka Y.; Ghazali M.J. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Titanium-coated ceramic materials with varying roughness and surface topography have been developed and utilized in clinical trials within the realms of medical and dental implantology. The objective of this study was to assess how cellular attachment is affected by the surface porosity and roughness of the titanium alloy (Ti-6Al-4V) coated with titania (TiO2)-reinforced yttria-stabilized zirconia (YZP). Additionally, the wettability of different types of TiO2-coated YZP was also evaluated for its effect on cellular migration and attachment. The results showed excellent adhesion between fibroblast cells and the surface of the YZP/TiO2 coating, with TiO2 reinforcement exhibiting bioactive properties that promote rapid cell growth and reproduction. Despite its average micro surface roughness measuring 5.86 0.36 m, the YZP/TiO2 surface coating demonstrated superior suitability for both fibroblast cell adhesion and the promotion of osseointegration. The YZP coating with 30% TiO2 demonstrated the most desirable properties, significantly enhancing biocompatibility. This study can serve as a basis for determining the biocompatibility and bioactivity of the YZP/TiO2 coating, which holds promise as a new coating material. 2023 by the authors.